Factors That Affect The Performance Of Matahari Lima Posyandu Kader In Providing Excellent Service In RT 001 RW 03 Village Sunter Agung North Jakarta - Ria Efkelin; Yurita Mailintina; Martini, Martini; Lipin, Lipin (Sean Institute, 2024)
Kader are included as catalysts in the Community Empowerment Process in providing support and providing assistance in the process of monitoring, evaluating, and approaching the implementation of Community Empowerment. Kader play a role as community mobilizers in utilizing health services, managing UKBM, health counseling to the community, recording activities and reporting if there are problems related to health. If the kader are not active, the Posyandu will be hampered so that the community lacks health intake which will result in the nutrition of toddlers because it cannot be detected early clearly. The purpose of this study is to find out the Factors That Affect The Performance Of Matahari Lima Posyandu Kader In Providing Excellent Service In Rt 001 Rw 03 Village Sunter Agung North Jakarta, seen from the benefits of posyandu. The research method used was quantitative with a cross sectional design involving 30 respondents. Research Results: Efforts need to be made to increase the level of knowledge, motivation, and infrastructure of Posyandu kader, as well as increase family support for Posyandu kader in providing excellent service.